Multiregion human bladder cancer sequencing reveals tumour evolution, bladder cancer phenotypes and implications for targeted therapy. Issue 2 (18th March 2019) - Heide, Timon; Maurer, Angela; Eipel, Monika; Knoll, Katrin; Geelvink, Mirja; Veeck, Juergen; Knuechel, Ruth; van Essen, Julius; Stoehr, Robert; Hartmann, Arndt; Altmueller, Janine; Graham, Trevor A; et al.
Abstract: We present an evolutionary analysis of the relative time of genetic events underlying tumorigenesis in human bladder cancers from 10 whole cystectomy specimens using multiregional whole‐exome sequencing. We timed bladder cancer drivers, mutational signatures, ploidy and copy number alterations, provided evidence for kataegis and correlated alterations with tumour areas and histological phenotypes. We found that: (1) heterogeneous tumour areas/phenotypes had distinct driver mutations, (2) papillary‐invasive tumours divided early into two parallel evolving branches and (3) parallel evolution of subclonal driver mutations occurred. APOBEC mutational signatures were found to be very early events, active in carcinoma in situ, and often remained a dominant source of mutations throughout tumour evolution. Genetic progression from carcinoma in situ followed driver mutations in NA13/FAT1, ZBTB7B or EP300/USP28/KMT2D . Our results point towards a more diverse mutational trajectory of bladder tumorigenesis and underpin the importance of timing of mutational processes and clonal architecture in bladder cancer as important aspects for successful prognostication and therapy. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.